2016
DOI: 10.1039/c6ra03507h
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oxidase/peroxidase-like activities of aptamer conjugated MoS2/PtCu nanocomposites and their biosensing application

Abstract: Taking advantage of bimetallic alloy nanoparticles and MoS2 nanosheets, a colorimetric aptasensor was developed for MUC1 overexpressed cancer cell detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…With a substrate of either TMB or H 2 O 2 , the bimetallic nanocomposites gave both lower K m values and larger V max values ( Table 1) than those of monometallic ones, indicating better affinity and POD-like activity by introducing bimetallic NPs into g-C 3 N 4 NSs. Similar observations were obtained by Pt/CuO (Wang X. H. et al, 2017), IrO 2 /rGO (Liu X. L. et al, 2019), Pd/NiCl 2 (Cai et al, 2018a), and PtM/MoS 2 (M = Ag, Cu, and Au) (Cai et al, 2016(Cai et al, , 2017Qi et al, 2016) as reported by our group.…”
Section: Enzymatic Properties Of 2d Nanozymes Pod-and Od-like Propertiessupporting
confidence: 89%
See 2 more Smart Citations
“…With a substrate of either TMB or H 2 O 2 , the bimetallic nanocomposites gave both lower K m values and larger V max values ( Table 1) than those of monometallic ones, indicating better affinity and POD-like activity by introducing bimetallic NPs into g-C 3 N 4 NSs. Similar observations were obtained by Pt/CuO (Wang X. H. et al, 2017), IrO 2 /rGO (Liu X. L. et al, 2019), Pd/NiCl 2 (Cai et al, 2018a), and PtM/MoS 2 (M = Ag, Cu, and Au) (Cai et al, 2016(Cai et al, , 2017Qi et al, 2016) as reported by our group.…”
Section: Enzymatic Properties Of 2d Nanozymes Pod-and Od-like Propertiessupporting
confidence: 89%
“…For example, Yang's group found that the few-layer MoS 2 NSs prepared by liquid-exfoliation exhibited ternary activities (POD-, OD-, and CAT-like activities) (Chen T. M. et al, 2018). As discussed above, these enzymatic activities could be closely associated with specific reaction conditions especially system pH, in which the acidic conditions are usually favorable for POD/OD-mimic catalysis (Qi et al, 2016;Cai et al, 2017;Darabdhara et al, 2019;Feng et al, 2020), while a high pH is beneficial to CAT-catalysis (Liu Y. et al, 2014;Ruan et al, 2018;Wang et al, 2019). Due to the use of various 2D NMs in biomedical fields, for a meaningful discussion of enzymelike activity, the reaction parameters, nature of materials (e.g., morphology, structure, composition, and size), capping agents, and surface charge, are believed to be taken into account .…”
Section: Sod-and Cat-like Propertiesmentioning
confidence: 98%
See 1 more Smart Citation
“…[112][113][114] A novel MoS 2 /PtCu nanocomposite with excellent OXD-like activity has been constructed for detection of cancer cells. 74 The nanocomposites quickly catalyzed the oxidation of three common chromogenic substrates such as TMB, ABTS, and OPD in the presence of dissolved oxygen in solution, producing typical colors. On the basis of OXD-like activity of MoS 2 /PtCu and mucin 1 (MUC1) aptamer, selective binding of aptamer-conjugated MoS 2 /PtCu aptasensor (apt-MoS 2 /PtCu) on the MUC1overexpressed cells converted the recognition process into a quantitative colorimetric signal.…”
Section: 1mentioning
confidence: 99%
“…A novel bimetallic platinum–copper nanoparticle‐decorated MoS 2 composite was synthesized by Qi et al. [ 239 ] for the colorimetric detection of cancerous mucin 1 (MUC1) overexpressed cells. The colorimetric biosensor was fabricated by functionalizing the composite with MUC1 aptamers.…”
Section: Optical Sensors Based On 2d Materials Compositesmentioning
confidence: 99%